2019
DOI: 10.33368/woh.v0i0.136
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Factors Affecting Anxiety In Pregnant Women On Sexual Relations at RSIA Siti Khadijah I Makassar

Abstract: Sexual relations are a primary need for married couples. However, many couples who disagree about sex during pregnancy are caused by anxiety from each partner. The general purpose of this research is to analyze the factors that influence anxiety in pregnant women against sexual relations in RSIA Sitti Khadijah 1 Makassar City.This research approach is observational, with a cross sectional approach. The population in this study were all pregnant women in RSIA Sitti Khadijah 1, Makassar City. The sample in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Penelitian ini sejalan pula dengan penelitian Nelcy, dkk bahwa ibu hamil cenderung mengalami kecemasan ketika melakukan hubungan seksual. 16 Hasil uji Independent Sample T-Test pada masing-masing trimester didapatkan nilai t = 2.745 dan p-value= 0.008 (p<0.05) pada trimester satu, kemudian pada trimester kedua didapatkan nilai t = -2.436 dan p-value=0.018 (p<0.05), sedangkan pada trimester ketiga didapatkan nilai t =3.012 dan p-value=0.004 (p<0.05) sehingga dapat disimpulkan terdapat perbedaan tingkat kepuasan seksual pada pasangan suami istri pada tiap trimester.…”
Section: Perbedaan Hubungan Seksual Sebelum Dan Saat Mengalami Kehamilanunclassified
“…Penelitian ini sejalan pula dengan penelitian Nelcy, dkk bahwa ibu hamil cenderung mengalami kecemasan ketika melakukan hubungan seksual. 16 Hasil uji Independent Sample T-Test pada masing-masing trimester didapatkan nilai t = 2.745 dan p-value= 0.008 (p<0.05) pada trimester satu, kemudian pada trimester kedua didapatkan nilai t = -2.436 dan p-value=0.018 (p<0.05), sedangkan pada trimester ketiga didapatkan nilai t =3.012 dan p-value=0.004 (p<0.05) sehingga dapat disimpulkan terdapat perbedaan tingkat kepuasan seksual pada pasangan suami istri pada tiap trimester.…”
Section: Perbedaan Hubungan Seksual Sebelum Dan Saat Mengalami Kehamilanunclassified
“…4 Penelitian ini sejalan pula dengan penelitian Nelcy, dkk bahwa ibu hamil cenderung mengalami kecemasan ketika melakukan hubungan seksual. 16 Hasil uji Independent Sample T-Test pada masing-masing trimester didapatkan nilai t = 2.745 dan p-value= 0.008 (p<0.05) pada trimester satu, kemudian pada trimester kedua didapatkan nilai t = -2.436 dan p-value=0.018 (p<0.05), sedangkan pada trimester ketiga didapatkan nilai t =3.012 dan p-value=0.004 (p<0.05) sehingga dapat disimpulkan terdapat perbedaan tingkat kepuasan seksual pada pasangan suami istri pada tiap trimester.…”
Section: Pembahasan Tinjauan Dari Kondisi Fisik Perubahan Frekuensi H...unclassified
“…For example, this change in body shape can cause fear and anxiety when facing childbirth for the first time. 3 The relationship between the anxiety level of pregnant women and the risk of giving birth to a low birth weight baby in IndonesiaPublic health centerrappang. Based on this research, it was found that the majority of pregnant women had mild anxiety as many as 22 people (73.0%), moderate anxiety as many as 4 people (13.0%) and as many as 3 people did not experience anxiety (3.0%) which means that most Most pregnant women have mild anxiety during their pregnancy.Pregnancy anxiety refers to worries and fears about pregnancy and the health of the baby.…”
Section: Introductionmentioning
confidence: 99%